Abnormal cortical morphology in children and adolescents with intermittent exotropia - Wang, Xi; Lu, Lu; Liao, Meng; Wei, Hong; Chen, Xiaohang; Huang, Xiaoqi; Liu, Longqian; Gong, Qiyong (Frontiers in Neuroscience, 2022)
Purpose: To investigate cortical differences, age-related cortical differences, and structural covariance differences between children with intermittent exotropia (IXT) and healthy controls (HCs) using high-resolution magnetic resonance imaging (MRI). Methods: Sixteen IXT patients and 16 HCs underwent MRI using a 3-T MR scanner. FreeSurfer software was used to obtain measures of cortical volume, thickness, and surface area. Group differences in cortical thickness, volume and surface area were examined using a general linear model with intracranial volume, age and sex as covariates. Then, the age-related cortical differences between the two groups and structural covariance in abnormal morphometric changes were examined. Results: Compared to HCs, IXT patients demonstrated significantly decreased surface area in the left primary visual cortex, and increased surface area in the left inferior temporal cortex. We also found increased cortical thickness in the left orbitofrontal cortex, right middle temporal cortex, and right inferior frontal cortex. No significant differences were found in cortical volume between the two groups. There were several negative correlations between neuroanatomic measurements and age in the HC group that were not observed in the IXT group. In addition, we identified altered patterns of structural correlations across brain regions in patients with IXT. Conclusion: To our knowledge, this study is the first to characterize the cortical morphometry of the patients with IXT. Based on our results, children and adolescents with IXT exhibited significant alterations in the primary visual cortex and association cortices, different cortical morphometric development patterns, and disrupted structural covariance across brain regions.